Secondary school teachers and mental health competence: Italy–United Kingdom comparison. Issue 3 (11th May 2016) - Monducci, Elena; Battaglia, Claudia; Forte, Alberto; Masillo, Alice; Telesforo, Ludovica; Carlotto, Alessandra; Piazzi, Gioia; Patanè, Martina; De Angelis, Giulia; Romano, Antonio; Fagioli, Francesca; Girardi, Paolo; et al.
Abstract: Aim: The aim of this study was to evaluate the differences between teachers' knowledge about early psychosis among three different Italian cities and a UK sample. Methods: The sample consisted of 556 secondary school teachers from three different cities in Italy (Milan, Rome and Lamezia Terme) and London (UK). The research was based on the Knowledge and Experience of Social Emotional Difficulties Among Young People Questionnaire. The Italian version of the questionnaire was used in Italy. Results: Overall, 67.6% of English teachers, 58.5% of Milan's teachers, 41.8% of Rome's teachers and 33.3% of Lamezia Terme's teachers were able to recognize psychotic symptoms from a case vignette. Logistic regression analysis showed that 'city' was the only independent variable significantly related to the correct/wrong answer about diagnosis. Conclusions: We found statistically significant differences between the three Italian samples and the UK sample regarding teachers' knowledge about first signs of psychosis. English teachers showed a better knowledge than Italian teachers in general. Teachers from Milan, where a specific early detection program was established in 2000, seemed to be more familiar with early signs of psychosis than teachers in the other two Italian towns.